Internet connectivity disruption in Pakistan (Pakistan) - Voidly (2026)
CRITICAL severity disruption detected in Pakistan. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: PK-2026-0118
Keywords: internet disruption; PK; disruption; critical